(untitled) (Journal of Medicine, 2023)
Overall, knowledge on breast cancer acts as a decision maker for medical help seeking during disease diagnosis and treatment. With this study we determined the impact of knowledge on breast cancer and related causes. A cross sectional study was conducted among newly diagnosed breast cancer patients National Institute of Cancer Research and Hospital, Dhaka from July 2017-June 2018. Face to face interview was taken by pretested semi structured questionnaire asking every breast cancer woman regarding knowledge and practice on sign-symptom, Breast-Self-Examination and mammography. After symptom identification first consultation to health care provider was a critical point and homeopathy was the major mean of first consultation. Breast cancer patients did not know the symptoms might cause cancer and as well negligence also play a role in help seeking. Improved knowledge can increase awareness as well influence practice on Breast-Self-Examination. To overcome this problem massive program is needed for early diagnosis and treatment. J MEDICINE 2023; 24: 23-27